Asas Kemandirian Notaris Berdasarkan Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris - Yulia Putri, Rada (Green Publisher Indonesia, 2025)
In the midst of the dynamics of modern legal developments, the principle of notary independence is the key to maintaining the integrity of legal documents and preventing interventions that undermine the neutrality of the notary function. This study aims to analyze and identify the character of notary independence based on the Notary Position Law, as well as to examine the legal consequences arising from the non-fulfillment of the principle of independence in the implementation of notary duties. The method used is a juridical-normative approach through literature study and analysis of relevant legal documents, so that legal norms, doctrines, and the application of the principle of independence can be described systematically. The results of the study show that notaries have a vital role in ensuring the validity and authenticity of deeds through the application of the principle of independence enforced by legal regulations, while the inindependence of notaries can have serious legal impacts, such as administrative sanctions and criminal prosecutions, which have the potential to erode public trust. Overall, the study concludes that the principle of independence is an important foundation in the implementation of notary duties in a neutral and professional manner, so the enforcement of this principle must continue to be strengthened to maintain the integrity and public trust in notary institutions.